Market Function through Small Family Farms-Middleman Interaction, and Its Relation to Food Security: Evidence from Indonesia - Endar Purnawan; Yuliska; Gianluca Brunori; Natalia Gabriela Molina (International ABEC, 2021)
This research addresses the interaction between small family farms and middleman and its relation to food security. Based on a qualitative method analysis derives from farmer and intermediaries interviews, this research sheds light on four types of middleman in this area: conventional middleman, rice middleman, banana middleman, and rubber middleman. It reveals factors motivating farmers to market crops through a middleman such as best crops selling price, the quantity of the crops, a new market for subsistence crops, and tied relationship. The result indicates that each middleman's role differs depending on the interaction, where most of them are simply a way to connecting farmers to the final market to earn cash quickly. Taken together, the research findings highlight the role of each middleman, including